IN VITRO EVALUATION OF ANTHELMINTIC ACTIVITY OF AQUEOUS EXTRACT OF ARDISIA COLORATA ROXB. LEAVES IN ADULT EARTHWORMS - SARKAR, PRASENJIT; DEVI, N. MEENA; MEETEI, U. DHARMARAJ; V., GOBINATH (International Journal of Current Pharmaceutical Research, 2023)
Objective: The study aims to evaluate the anthelmintic activity of aqueous extract of Ardisia colorata Roxb. leaves (AQEAC) using adult earthworms (Pheretima posthuman). Methods: The total of 24 adult earthworms were divided into four groups, with six worms in each group (n=6). The anthelmintic activity of AQEAC at two different doses (25 mg/ml and 50 mg/ml) was evaluated by assessing the time of paralysis (min) and time of death (min) of the earthworms. Albendazole (25 mg/ml) was used as standard and 2% gum acacia as control. Results: The result showed that AQEAChad significant anthelmintic activity (p<0.001) in a dose-dependent manner but was less potent than the standard drug albendazole. Conclusion: AQEAC demonstrated significant anthelmintic activity but was less potent than the standard drug albendazole. However, further studies with higher doses are required to evaluate the dose-dependent activity and to evaluate the exact mechanism responsible for anthelmintic activity.